Fragmentation and Vulnerability of Oueme - Boukou Classified Forest Plants (east – Center of Benin) - TCHIBOZO, ERIC ALAIN MAHUGNON; DOMINGO, ETIENNE; SOHOU, Brice (My University, 2014)
This article aims to assess the fragmentation level of Ouémé - Boukouclassified forest and analyze the vulnerability of itsvegetationplants. The methods used are made up of a multidisciplinary approach, based on the photo - interpretation by visual enhancement and image assisted classification, lineaments photo - interpretation, spatial analysis and digital mapping. The results obtained show that Ouémé - Boukou classified forest is covered by a 46.35% of the wet vegetation (20.75% water), unevenly distributed and under the pressure of natural factors (27.08% for flooding, 21.43% for the differential soil erosion, 17.89% for the weathering of rocks, 17.24% for the network of fractures and lineaments) and anthropogenic factors (16.36% for mosaic crops and fallow). The vulnerability of vegetation plant is varied and depends on factors considered. For all factors, the grassland is the most affected (37.31% for the flood, 33.43% differential soil erosion, 39.69% for the weathering of rocks, 35.00% for the network of fractures and lineaments and 34.64% for the mosaic of cultures and fallow). A portion of all vegetation (44.45% or 1,012.94 hectares) is fragmented islands with less than 25 hectares. Savanna and gallery forest are the most fragmented below this threshold habitats. This situation indicate that the forest structure and biodiversity are fast, deep and lasting affected.
Keywords: fragmentation; Oueme-Boukouclassified forest; vulnerability; vegetation plants.